Formation mechanism and stability of austenitic islands in carbides in a Ni-Cr-Fe based high-temperature austenitic alloy undergoing carburization. (May 2021) - Shu, Shipeng; Hu, Xiaobing; Kazemzadeh-Atoufi, Maryam; Liu, Tao; Shang, Anyu; Davis, Mark B.; Ziebarth, Robin; Dhingra, Sandeep; Morgan, Robert D.; Du, Yao; Voorhees, Peter W.; Seidman, David N.
Abstract: We investigate a phase transformation in a Ni-Cr-Fe-based high-temperature alloy during the technologically important carburization process, with multi-length scale experimental techniques. The study focuses on the formation and stability of novel austenitic islands formed within carbide structures during the M23 C6 to M7 C3 phase-transformation. We demonstrate that the austenitic islands nucleate near the M23 C6 /M7 C3 transformation front, from a supersaturation of metal atoms in the M23 C6 -carbide as M7 C3 grows. After formation, the austenitic islands equilibrate their composition with the matrix temporally but remain relatively stable inside the carbides due to their large sizes (a few hundred nanometers in diameter) and a weak Gibbs-Thomson effect. Graphical abstract: Image, graphical abstract